Pendampingan Penyusunan Rancangan Paket Wisata Menggunakan Metode Analisis Value Chain pada Wisata Kampung Warna-Warni Jodipan - Hanif Rani Iswari; Khojanah Hasan; Zulkifli; Ika Fitria Nur Hamida; Lely Dista Safitri; Maya Ratnasari (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Jodipan Colorful Village (KWJ) in Malang City has become an attractive tourist destination, changing its image from a slum village to a beautiful and clean village. The community service program with the title "Assistance in the Preparation of Tour Package Designs Using the Value Chain Analysis Method in Jodipan Colorful Village Tourism" aims to increase the attractiveness and income of tourism in KWJ through the preparation of tour packages. Jodipan Colorful Village (KWJ) in Malang City has succeeded in achieving a significant increase in tourist attraction and income through a mentoring program that focuses on preparing tour packages. First, in the data collection stage through Focus Group Discussion (FGD), KWJ's key values were identified: aesthetics, education and social interaction. The results of the FGD provide an overview of these values, forming the basis for formulating tour package ideas. Second, the implementation stage is carried out with assistance from the service team to the KWJ management. By using the value chain analysis method, tourism package ideas such as educational, social and culinary are generated. This process involves understanding activities that create added value for tourists, optimizing resource utilization and increasing efficiency. Third, trials and launching are carried out involving tourism stakeholders. Tour packages are tested on tourists, and the results are used for improvement. The launch was carried out via social media to increase promotion. This program succeeded in formulating 4 tour packages (Color Package, Warni Package, Jodipan Package, KWJ Package) based on the results of value chain analysis. The results are supported by positive responses from tourists during trials and launching, showing high potential attraction.